Correction of the Mitochondrial NADH Oxidase Activity, Peroxidation and Phospholipid Metabolism by Haplogenin-7-Glucoside in Hypoxia and Ischemia - Umidakhon, Yusupova; Erkin, Botirov; Ulugbek, Gayibov; Bahadir, Niyazmetov; Karim, Almatov (Trends in Sciences, 2022)
In this study, it was used haplogenin-7-glucoside flavonol (C16H12O8) isolated from the plant Haplophyllum perforatum. It was studied the effect of haplogenin-7-glycoside on NADH oxidase activity, peroxidation, and phospholipid metabolism in rat liver mitochondria under in vitro conditions. Incubation of mitochondria at 37 ℃ leads to disruption of the integrity of mitochondrial membranes, as a result, in cytochrome с desorption from the inner membrane into the intermembrane space, which leads to a decrease in the activity of rotenone-sensitive NADH oxidase and an increase in the activity of rotenone-insensitive NADH oxidase. Haplogenin-7-glucoside exhibits membrane stabilization by reducing these alterations. Under ischemia conditions, the effect of haplogenin-7-glucoside on the LPO process in mitochondria decreases LPO in mitochondria. Quantitative changes in phosphatidylserine in mitochondrial membranes under LPO conditions during incubation of mitochondria at 37 ℃ were observed to accelerate controlled (auto-oxidation) LPO over time (0 - 90 min). Peroxidation of phosphatidylserine in mitochondria when the addition of haplogenin-7-glucoside to the incubation medium at 30, 60 and 90 min, LPO was found to be reduced. The increasing amount of phosphatidylinositol has not happened depend on time. However, a slight increase was found under the influence of haplogenin-7-glucoside. HIGHLIGHTS Cytochrome c desorption from the inner membrane into the interstitial space leads to a decrease in the activity of rotenone-sensitive NADH-oxidase and an increase in the activity of non-rotenone-sensitive NADH-oxidase Haplogenin-7-glycoside showed membrane-stabilizing properties by significantly reducing these changes; the addition of haplogenin-7-glucoside to mitochondria leads to a decrease for MDA, a decrease in the LPO process At incubation of mitochondria at 37℃, the amount of phosphatidic acid and lysophosphatidic acid in mitochondria under LPO conditions was also found to be less than control under the influence of haplogenin-7-glucoside. Thus, haplogenin-7-glucoside reduces the rate of peroxidation of phospholipids in liver mitochondria and has a corrective effect GRAPHICAL ABSTRACT